ENTREPRENEURIAL EDUCATION DAN ENTREPRENEURIAL INTENTION: SOCIAL SUPPORT SEBAGAI MODERASI VARIABEL - Rahmah, Yulia Fithriyani (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Research in entrepreneurship field has magnetized the interest of many researchers as a tool of development for many countries. This study examined the impact of social support as moderating variable between entrepreneurial education and entrepreneurial intention in Bandung. To achieve the above objective a survey of over 130 graduate students at four of the State University in Bandung. Data analysis using the Statistical Product Solution Service. Furthermore, multivariate analysis of variance was applied on the data. The results demonstrate that social support as moderating variable between entrepreneurial education and entrepreneurial intention. There is a positive moderating effect of social support on the entrepreneurial education and entrepreneurial intention. High social support is associated with a positive relation entrepreneurial education and entrepreneurial intention, while low social support is associated with no relation or even a negative relation between entrepreneurial education and entrepreneurial intention.